Communication Strategies Within DKI Jakarta Government's Policy Aim to Address Waste Management Challenges Effectively - Hananuraga, Rahula; Khoong Tai Wai; Abdul Kholik; Jeni Kwang (International Journal of Environmental Communication (ENVICOMM), 2023)
Waste remains a recurring issue in DKI Jakarta. This study investigates how the government communicates information regarding waste management to shape public perception on waste issues through media platforms, utilizing content analysis from social media and other online news sources. Agenda setting theory is employed to understand how the government prioritizes waste problems and the level of public attention towards these issues. The research methodology adopts a qualitative descriptive approach using secondary data sources through document analysis. Data was collected from social media posts containing keywords related to waste and its management over the past two years. The study findings indicate that the government has conducted various public education campaigns aimed at enhancing public awareness of the importance of effective waste management.